The Islamic Education Curriculum that Focuses on Moral Development in a Hadith Perspective - Rahma Nadiyah; Ramdhani, Muhammad Rendi (Edupedia Publisher, 2024)
The purpose of this study is to find out an overview of how the Islamic education curriculum focuses on moral development in the perspective of the hadith of the Prophet Muhammad SAW. The type of research used in this study is using qualitative methods and library research which processes literature-based data, while the source of literature in this article is a journal that is relevant to the research And the approach used is content analysis by studying the material descriptively and in depth. The results of this study show that all the hadiths about morals listed in this study contain guidance for the practice of noble moral values that are urgently needed by every Muslim in his life in this world, related to his relationship with Allah and his interaction with fellow creatures.